Ensemble Plus-Minus and Leafcutter John at Kammer Klang, Cafe Oto, London. (20th March 2014) - Graham, Stephen
Abstract : It would be simplistic to suggest that contemporary classical music exists solely within or around large institutions. For at least 50 years now, this music has also found a home in small galleries, loft spaces and basements, and other small, independent venues around the world, as seen for example in the Downtown New York scene. London venue Cafe Oto – operating out of a warehouse in Dalston since 2008 – runs on similar principles to specialist Downtown venues such as the Stone, in that it boasts a wide-ranging multi-genre programme focused on various experimental and avant-garde musics, such as noise, free jazz, and contemporary classical.